2021
DOI: 10.9734/irjpac/2021/v22i1030439
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening, Total Phenolics Content and Antioxydants Potential of Different parts of Grangea maderaspatana from Burkina Faso

Abstract: This work is a contribution to a better use of Grangea maderaspatana belonging to family Asteracea as a medicinal plant for its phytochemicals.  Extracts of different parts of Grangea maderaspatana were thus screened for their phytochemicals, including phenolics, tannins and flavonoids contents and total antioxidant contents. The extracts were obtained from the roots, flowers, leafy branches and the whole plant using hexane, dichloromethane, ethyl acetate and methanol. The phytochemical screening was car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…According to the work of Kouassi and al., the methanolic extracts of the leaves and flowers of C. giganteus contained the best levels of total phenolic compounds (118.14 mg GAE/g of extract) [26] . The phenolic compound contents of the methanolic and ethyl acetate extracts of Acanthospermum hispidum remain higher than those reported by Yougoubo Abdoulaye et al in this work on the leafy branches of G. maderaspatana where the contents were 57.921 and 12.260 mg GAE/g of extract respectively for the ethyl acetate and methanol extracts [27] .…”
Section: Total Phenolics Content (Tpc)contrasting
confidence: 75%
See 2 more Smart Citations
“…According to the work of Kouassi and al., the methanolic extracts of the leaves and flowers of C. giganteus contained the best levels of total phenolic compounds (118.14 mg GAE/g of extract) [26] . The phenolic compound contents of the methanolic and ethyl acetate extracts of Acanthospermum hispidum remain higher than those reported by Yougoubo Abdoulaye et al in this work on the leafy branches of G. maderaspatana where the contents were 57.921 and 12.260 mg GAE/g of extract respectively for the ethyl acetate and methanol extracts [27] .…”
Section: Total Phenolics Content (Tpc)contrasting
confidence: 75%
“…These results are in agreement with the work of Remy K Bationo and al., [25] . In addition, the work of Yougoubo Abdoulaye and al., carried out on the extracts of the leafy branches of G. maderaspatana showed that the ethyl acetate extract contained the best content of total phenolic compounds (57.921 mg GAE/g of extract) followed by the methanol extract (12.260 mg GAE/g extract) and the antioxidant levels were in the same order with 13.209 and 11.355 mg TE/g extract respectively [27] .…”
Section: Antioxidant Content (Aoc)mentioning
confidence: 91%
See 1 more Smart Citation